Exploring Factors Influencing Purchase Decisions: A Case Study of a Rapidly Growing Bakery: Menganalisis Dampak Citra Merek, Kepercayaan Merek, Kualitas Produk, dan Harga terhadap Keputusan Pembelian: Studi Kasus Sebuah Toko Roti yang Berkembang Pesat - Devan Kertajasa; Rita Ambarwati Sukmono (Universitas Muhammadiyah Sidoarjo, 2022)
This research examines the influence of brand image, brand trust, product quality, and price on the purchase decisions of consumers in a rapidly growing bakery, Kampoeng Roti Tropodo, Sidoarjo. A quantitative research approach was employed, utilizing a questionnaire-based survey conducted with 100 consumers of Kampoeng Roti in Tropodo, Sidoarjo. The Likert scale was used to measure the variables, and multiple linear regression analysis was performed using IBM Statistical Package for the Social Sciences (SPSS) version 24. The findings reveal that brand image, brand trust, product quality, and price individually exert a significant influence on the purchase decisions. Moreover, when considered collectively, these factors have a significant impact on purchase decisions. The implications of these results highlight the importance of managing brand image, building trust, maintaining product quality, and pricing strategies to enhance purchase decisions for businesses operating in the competitive bakery market. Highlights: The study examines the impact of brand image, brand trust, product quality, and price on purchase decisions in a rapidly growing bakery. Each factor individually influences the purchase decisions of consumers in the bakery industry. When considered together, brand image, brand trust, product quality, and price significantly affect purchase decisions, emphasizing the importance of these factors in bakery marketing strategies. Keywords: Brand Image, Brand Trust, Product Quality, Price, Purchase Decisions